An Integrated Silicon Photonic Chip for Continuous-Variable Quantum Random Numbers Generator Based on Vacuum Fluctuation. Issue 2 (April 2021) - Zhu, Menglin; Wang, Xiangyu; Xu, Bingjie; Yu, Song; Chen, Ziyang; Guo, Hong
Abstract: The deployment of quantum random number generator in fiber optics is strongly limited in real world applications due to the size of the components and their cost. Here we present a quantum random number generator based on vacuum fluctuation using an optical homodyne detection in silicon photonic chip achieving minimum entropy/bit of 8.5 for 10 bits sample. The produced random numbers have passed all NIST randomness tests.